2014
DOI: 10.1186/1478-4505-12-60
|View full text |Cite
|
Sign up to set email alerts
|

Does knowledge of danger signs of pregnancy predict birth preparedness? A critique of the evidence from women admitted with pregnancy complications

Abstract: BackgroundImproved knowledge of obstetric danger signs, birth preparedness practices, and readiness for emergency complications are among the strategies aimed at both enhancing utilization of maternal health services and increasing access to skilled care during childbirth, particularly for women with obstetric complications. It is unclear whether knowledge of danger signs translates into improved birth preparedness and complication readiness. The objective was to assess the association between knowledge of dan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

18
71
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 80 publications
(97 citation statements)
references
References 33 publications
(30 reference statements)
18
71
7
1
Order By: Relevance
“…Studies conducted in Sub-Saharan Africa have reported low levels of maternal and newborn care knowledge and birth preparedness practices among women [6,1417]. In Eastern Uganda, a study revealed that only 25% of respondents had at least three components of the birth plan [10], while in rural communities of Western Uganda, only 19% had knowledge of three or more key danger signs during pregnancy, delivery, and the postpartum period [11].…”
Section: Introductionmentioning
confidence: 99%
“…Studies conducted in Sub-Saharan Africa have reported low levels of maternal and newborn care knowledge and birth preparedness practices among women [6,1417]. In Eastern Uganda, a study revealed that only 25% of respondents had at least three components of the birth plan [10], while in rural communities of Western Uganda, only 19% had knowledge of three or more key danger signs during pregnancy, delivery, and the postpartum period [11].…”
Section: Introductionmentioning
confidence: 99%
“…3,4,15 The IBP concept is based on the assumption that lack of it or lack of awareness of it may lead to delay in seeking care, delay in transportation to a health facility and delay in receiving care from a skilled health provider and the possibility of resulting into undesirable birth outcomes both to the mother and baby. 6 In Kenya giving birth is free in public health facilities. However, the decision to seek care and arranging for transport, is the sole responsibility of the client and her family.…”
Section: Determinants Of Ibp Utilizationmentioning
confidence: 99%
“…6,8,9 Women who are well prepared and have knowledge on danger signs in pregnancy, are more likely to: identify a skilled birth attendant, be financially ready to meet emergency costs and transportation and be ready with a potential blood donor thus improving chances of a positive birth outcome. 4,6,8,9 A number of socio-demographic factors have been found to be associated with birth-preparedness such as level of education; however, little is known on how socioecologic factors such as attitudes and perceptions of clients determine utilization of IBP in a rural area. 7,9 There is some evidence clients perceive birth preparedness negatively.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations